Remission game: A psychological support among depressive cancer patients - Sehrish Khan; Shagufta Perveen; Rukhsana Y. Maroof (The Journal of Humanities & Social Sciences, 2022)
Trend to use video games in health sector is increasing day by day. Many games are designed to provide psychological support to patients suffering from chronic and progressive diseases. Remission-II game is designed to boost up the treatment process of cancer patients. Current study explored the effect of Remission Game on depressive symptoms of cancer patients. A pretest posttest approach is used to conduct this study on a sample of 60 cancer patients. All the participants were assessed with the help of Center for Epidemiological Studies Depression Scale for Children (CES-DC). Then they were randomly assigned to two equal groups, i-e control group and experimental group. 30 participants of experimental group played Remission-II game for a period of one month while the remaining 30 subjects of control group did not play any game. After a month, both groups were retested on CES-DC scale. Paired sample t-test was applied to compare the pretest and post-test scores of both groups. Results revealed significant difference in pretest and posttest results in experimental group while participants of control group revealed greater depression scores in posttest. Hence it was concluded that Remission game is an effective psychological support that can be used to decrease the depression level of cancer patients. Results of the study can be used to test the Remission game with other types of psychological problems as well.